表演藝術團體導入數位典藏之研究 A Study on the Development of Digital Archives for Performing Arts Groups - Hao-Ren Ke; Fang-Ling Lin (Jiàoyù zīliào yǔ túshūguǎn xué, 2012)
表演藝術孕育了豐富的文化資產,表演藝術團體運用有限的資源保存其作品,若表演藝術團體導入數位化,進行數位典藏,將能讓表演藝術此一豐富的文化資產得以長久保存。本研究採用質化研究方法,以半結構式深度訪談進行資料蒐集,共訪問十位受訪者,其中包含七家表演藝術團體、兩家學術單位與一家文化機構。本研究旨在探究已實施數位典藏之表演藝術團體的經驗,包括導入動機、導入前後工作流程與組織之差異及面臨之困難、後續效益與加值應用;對於未實施數位典藏表演藝術團體,則瞭解其未導入的原因及導入意願;對於曾與表演藝術團體合作數位典藏的學界或文化機構,則瞭解其與表演藝術團體合作數位典藏之方式。 Performing arts cultivates rich cultural assets. Performing arts groups utilize limited resources to reserve their works. If they can establish digital archives, rich cultural assets can be reserved for a long term. This study adopted the qualitative research approach and conducted semi-structured in-depth interviews to collect data. Ten interviewees, including seven performing arts groups, two academic departments and one cultural institution, were contacted. Through the interviews, this study attempts to investigate the experiences of performing arts groups which have created digital archives, including motivations, processes, organization change, difficulties, benefits, and value-added applications. For those which have not yet created digital archives, this study attempts to understand their reasons and thoughts. In addition, for academic and cultural institutions which have the experiences of cooperating with performing arts groups to establish digital archives, this article tries to understand the cooperation models.